Multi-Band Elastic Optical Networks: Inter-Channel Stimulated Raman Scattering-Aware Routing, Modulation Level and Spectrum Assignment - Mehrabi, Mahdieh; Beyranvand, Hamzeh; Emadi, Mohammad Javad (Journal of lightwave technology, 2021)
Recently, multi-band elastic optical networks (MB-EONs) have been introduced to increase the transmission capacity of optical networks by expanding the transmission frequency range beyond the conventional C-band (e.g., O-, E-, S-, and L-band). Thus, by utilizing the idle frequency bands of the existing standard single mode fibers (SMFs), the capacity improvement in MB-EONs is achieved with lower capital expenditure compared to other techniques, such as space division multiplexing (SDM) in multi-core fibers (MCFs). The routing, modulation level and spectrum assignment (RMLSA) problem in MB-EONs is more challenging than that of the conventional single band EONs, and the inter-channel stimulated Raman scattering (ISRS) process should be considered in signal-to-noise ratio (SNR) analysis. In this article, ISRS-aware RMLSA problem in MB-EONs is studied. We obtain the optimal solution of this problem by formulating a path-based integer linear programming (ILP) model. Since the number of slots and demands are too large in a multi-band system, the ILP problem is too complex to be solved in polynomial time. Therefore, we propose heuristic algorithms to solve the ISRS-aware RMLSA problem. Then, performance of the proposed schemes is evaluated through exhaustive simulations. The results reveal that among all the proposed heuristic algorithms, the algorithm named as enhanced in-process estimation (EIPE) has the best performance in saving more frequency slots for future demands, while achieving higher spectral efficiency and SNR estimation accuracy. Moreover, for a special case of small-scale scenario, the performance of EIPE is close to the results of ILP formulation. Finally, our results indicate that by ignoring ISRS process in the SNR estimation, outage occurs for some of lightpaths, where the outage percentage depends on the launch power.